Influence of age and quality of life on emotional health of secondary school teachers in Ilorin metropolis - Muraina, Kamilu Olanrewaju; Annor, Patricia Omioguele; Baba, Ayoku Oba (Journal of Education in Black Sea Region, 2022)
The purpose of this study was to examine the influence of age and quality of life on Kamilu Olanrewaju Muraina emotional health of secondary school teachers in Ilorin metropolis, Nigeria. The study adopted descriptive survey method of a correlation type. The population of this study comprised all secondary school teachers in Ilorin metropolis, Kwara state which was estimated to 9,298 while a sample of 425 secondary school teachers were selected for the study. The sample was selected using random sampling technique. Questionnaire titled “Age, Quality of Life and Emotional Health Questionnaire” (AQLEHQ) was used. It was content validated and tested with reliability coefficient of 0.85. Percentage was used for demographic data and research questions. Also mean, standard deviation and rank order analysis were used for research questions while two null hypotheses were tested using the Pearson’s Product Moment Correlation (PPMC) statistical tool. The findings revealed that the majority (72.3%) of the teachers in Ilorin metropolis had good emotional health and 57.5% of teachers in Ilorin metropolis had a high level of quality of life. The finding of the hypotheses revealed that age has no significant influence on the emotional health of secondary school teachers in Ilorin metropolis, Kwara state, but the quality of life has a significant influence on the emotional health of secondary school teachers in Ilorin metropolis, Kwara state. The study recommended the need for school authorities to plan an excellent quality of work life programme that will further enhance the overall quality of life of secondary school teachers with low quality of life.